Local effects on thermal comfort: Experimental investigation of small-area radiant cooling and low-speed draft caused by improperly retrofitted construction joints - Van Craenendonck, Stijn; Lauriks, Leen; Vuye, Cedric; Kampen, Jarl (Building and environment, 2019)
Improper attention to construction joints in a building may lead to localized cold spots on the inside surfaces of the building and air leakage through the envelope. This in turn can affect the thermal comfort of residents due to small-area radiant asymmetry and low-speed draft. The effect of these two local discomfort events on thermal comfort were investigated in two sets of experiments. The test setting consisted of a cool-to-neutral environment, in which a custom-built arrangement replicated small-area radiant asymmetry and low-speed draft caused by improper retrofitting of construction joints. Participants rated their thermal sensation and comfort for three consecutive test conditions associated with radiant asymmetry or draft. Each radiant asymmetry condition consisted of a combination of the height and temperature of a small cold spot and the distance between the cold spot and the subject. The draft conditions comprised the height of the draft outlet and the speed and temperature of the airflow. The heights of the cold spot and draft outlet correspond to the feet, chest and head level of a seated person. Draft perception was found to not be linked to the experimental parameters of the draft conditions, and as such was not impacted by improperly retrofitted construction joints. However, several statistically significant relationships were found between the radiant asymmetry parameters and thermal sensation. Nonetheless, these effects were very small, and the variance explained by these parameters was very low. Therefore, small-area radiant asymmetry cannot be used to make practical decisions in retrofitting strategies for construction joints. •Comfort experiments with 56 human subjects were performed.•Thermal sensation is influenced by gender, alcohol consumption and sleep quality.•Subjects are affected by radiant asymmetry in an unexpected way.•Draft is perceived most often in the arms region due to “falling” draft effect.•Speed and temperature of the airflow had no significant effect on draft perception.